Reflection of socio-political vocabulary in terminological dictionaries of the Kabardino-Circassian language - Khazhismel Ch. Zhiletezhev (Кавказология, 2025)
Russians Russian-Kabardian Terminological Dictionary for secondary School textbooks (1950) and the School Russian–Kabardian-Circassian Terminological Dictionary (1999), published on the basis of the Kabardian-Circassian language, were evaluated in the article. These works analyze one of the most poorly studied lexical and thematic groups of the Kabardian-Circassian language. – socio-political vocabulary. The main purpose of the work is a critical review of socio–political vocabulary in the terminological dictionaries of the Kabardino-Circassian language. To achieve this goal, the content, structure, and typical features of dictionaries are presented in detail, and their advantages and disadvantages are highlighted. The author focuses on the fact that in the Kabardino-Circassian language, in addition to the school terminological dictionaries under consideration, there are no such general terminological dictionaries. The analysis of the material allows us to establish that, although socio-political vocabulary is presented in sufficient quantity in the school dictionaries under consideration, there is still a discrepancy in spelling and interpretation of socio-political names.The novelty of the work lies in the fact that such a study of the terminology of the Kabardino-Circassian language is being conducted for the first time, there are no works on this topic either in Kabardino-Circassian or in Russian.The relevance of the research is due to the fact that many theoretical and practical issues related to the presentation of the socio-political vocabulary of the Kabardino-Circassian language in dictionaries require their solution. The paper uses a descriptive analytical method, contextual analysis, and statistical calculation.